Fault Tolerance Enhance DC-DC Converter Lifetime Extension - Alghassi, Alireza; Soulatiantork, Payam; Samie, Mohammad; Uriondo Del Pozo, Adrian; Perinpanayagam, Suresh; Faifer, M. (Elsevier, 2017)
One of the most crucial renewable energy sources today is solar energy. Power convertors play an important role in adjusting the output voltage or current of photovoltaic (PV) systems. Using efficient and reliable switches for power converters and inverters is crucial for enhancing the safety and reliability of a platform. Generally, power converters suffer from failure mechanisms, such as wire bond fatigue, wire bond lift up, solder fatigue and loose gate control voltage, which mainly occur in power switches. In this paper, the junction temperature of the Insulated Gate Bipolar Transistor (IGBT) acting as a power switch used in the Impedance-Source DC-DC converter is estimated using an electro-thermal model in order to develop an adaptive thermal stress control (ATSC). The proposed stress control adjusts reference input of the PI control to extend the life expectancy of the device under the mission. The accuracy of results present using The Modified Coffin-Manson Law has been used to determine the life of IGBT and the lifetime has been successfully increased base on implementing imperative ATSC and comparing the result with the constant reference input of the PI controller. The result integrates with converter health management to develop advanced intelligent predictive maintenance.
Keywords: Power Electronic Converter; EV; IGBT; Condition Base Monitoring (CBM); Remaning Useful Life (RUL); Prognostics; System Health Management (SHM)